Cross-reactivity of anti-human programmed cell death ligand 1 (PD-L1) monoclonal antibody, clone 28-8 against feline PD-L1 - KAGAWA, Yumiko; MIZUNO, Takuya; NISHIBORI, Shoma; IGASE, Masaya; UCHIDA, Kazuyuki; NAKAGAWA, Takayuki; SAKURAI, Masashi (Journal of Veterinary Medical Science, 2023)
Immunotherapy is a breakthrough in human cancer therapy and has become a major concern in veterinary oncology. However, in cats, many unclear points of the tumor microenvironment exist, including immune checkpoint molecules. A reason is that very few monoclonal antibodies have been proven to react with feline molecules. Therefore, this study investigated whether anti-human programmed cell death ligand 1 (PD-L1) monoclonal antibody, clone 28-8, which is currently commercially available, can also recognize feline PD-L1 by flow cytometry, immunoprecipitation, and immunohistochemical (IHC) staining. We confirmed that the antibody’s specificity by flow cytometry and immunoprecipitation using NIH3T3 cells transfected with feline PD-L1. Additionally, we revealed that PD-L1 was expressed on the surface of some feline cell lines by flow cytometry and clone 28-8 antibody unbound to the cells where feline PD-L1 was knocked out. Furthermore, IHC analysis revealed that PD-L1 was expressed in macrophages in the spleen and lymph nodes from healthy cats and mast cell tumor cells. Therefore, we indicated that the clone 28-8 antibody is a valuable tool in detecting feline PD-L1, and further analysis of tumor tissues is expected in the future.